Pengaruh Pengawasan Dan Kemampuan Kerja Terhadap Kinerja Pegawai Kejaksaan Tinggi Sumatera Selatan (Jurnal Manajemen dan Investasi (MANIVESTASI), 2020)
ABSTRACTÂ The problem of this research is the lack of a supervisory role that is not yet solid, and the goal is not yet achieved in the work ability to monitor and mobilize employees and the employee's performance is not optimal. This study aims to determine "The Effect of Supervision and Work Ability on Employee Performance of the South Sumatra High Prosecutor's Office".This research was conducted at the South Sumatra Prosecutor's Office. With a population of 75 people with a sample of all employees who live 75 people. The data collection techniques in this study were questionnaires and documentation. Data were analyzed using normality test, multicoloniarity, and heteroscedasticity test. And using simple linear regression hypothesis testing and multiple linear regression (determination, t test and f test).Based on the data analysis, it is known that the variables of Supervision and Work Ability jointly have a significant influence on the performance of the South Sumatra High Prosecutor's Office with a significance value of 0.000 (0.000